Monetary Policy and Exchange Rate Overshooting: Dornbusch Was Right After All - Hilde C. Bjørnland (Norges Bank, 2009)
Dornbusch's exchange rate overshooting hypothesis is a central building block in international macroeconomics. Yet, empirical studies of monetary policy have typically found exchange rate effects that are inconsistent with overshooting. This puzzling result has been viewed by some researchers as a "stylized fact" to be reckoned with in policy modelling. However, many of these studies, in particular those using VARs, have disregarded the strong contemporaneous interaction between monetary policy and exchange rate movements by placing zero restrictions on them. In contrast, we achieve identification by imposing a long-run neutrality restriction on the real exchange rate, thereby allowing for contemporaneous interaction between the interest rate and the exchange rate. In a study of four open economies, we find that the puzzles disappear. In particular, a contractionary monetary policy shock has a strong effect on the exchange rate, which appreciates on impact. The maximum effect occurs within 1-2 quarters, and the exchange rate thereafter gradually depreciates to baseline, consistent with the Dornbusch overshooting hypothesis and with few exceptions consistent with UIP.
hdl:11250/2497635
Keywords: C32; E52; F31; F41; 330; UIP; uncovered interest parity; structural VAR; Dornbusch overshooting; exchange rate; monetary policy